PENGARUH MEDIA PEMBELAJARAN BERBASIS LIVEWORKSHEETS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS III PADA PEMBELAJARAN IPAS SD N PRENGGUK II TAHUN AJARAN 2025/2026 - Zahra, Imroatun; Tukiyo; Rofisian, Nela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of Liveworksheets-based learning media on the science learning outcomes of third-grade elementary school students regarding the topic of the Life Cycle of Living Organisms. The study employed a quantitative approach using a quasi-experimental nonequivalent control group design. The sample consisted of 23 third-grade students from SD N Prengguk II as the experimental class and 23 students from SD N 1 Kadibolo as the control class. Data collection techniques included observation, pre-test and post-test assessments, and documentation. Data analysis involved validity, reliability, normality, and homogeneity tests, as well as an independent samples t-test. The results indicate that the use of Liveworksheets-based learning media significantly influences the learning outcomes of third-grade students at SD N Prengguk II. This is evidenced by the t-test results, which show that the calculated t-value of 4.321 is greater than the critical t-value of 2.018, indicating a significant effect following the implementation of Liveworksheets, with a significance level of 0.000 < 0.05, thus accepting the alternative hypothesis (Ha) and rejecting the null hypothesis (Ho). This significant effect is evident in the increased active engagement